Analysis of compensation and work environment in improving employee performance - Olivia, Marcella; Rizky, Muhammad Taufik; Ramadhani, Difa Alifiah (International Journal Labs, 2024)
Compensation is a key element that affects the performance of a company because it covers the emotional aspects of the workforce as well as the basic elements of accountability, logic, rationality, and worthiness. Compensation and the workplace have a significant impact on employee satisfaction with their jobs, according to research based on the design of writing challenges for this article, literature reviews, theoretical studies, reviews of results from related publications, and conceptual framework drawings. This article analyzed compensation and work environment in improving employee performance with a systematic review approach. The results of this study show that employee performance is positively influenced, significant, and insignificantly by pay and the work environment. Compensation has a positive impact on job satisfaction. This study provides several recommendations, such as paying all employees fairly and appropriately, giving them the opportunity to express their opinions, giving their opportunity to advance their careers, and, finally, offering training.